Graphene/MoXY Heterostructures Adjusted by Interlayer Distance, External Electric Field and Strain for Tunable Devices - Lijie Li (ACS Applied Nano Materials, 2019)
Graphene has shown great promise in many electronic devices and systems since it was discovered. However doping control limits its use in devices. For addressing this problem, graphene/MoXY (X/Y=S, Se, Te and X≠Y) heterostructures have been investigated in this work. We analyze electronic and optical properties of the graphene/MoXY heterostructures under various effects such as interlayer distance, external electric field and mechanical strain by the first principles method. We find that interlayer distance and external electric field are two prominent parameters to induce tunable homogeneous doping of graphene (G). Compared with interlayer distance modulation, the tuning range of the carrier density in the graphene layer by the external electric field is wider. In the graphene/MoXY heterostructures, the highest carrier density of graphene is simulated to be 4.62 x 10^13/cm^2 for the G/TeMoS stacking under the electric field strength of 1.0V/ Å. The doping concentration of the graphene layer can be tuned from 3.94 × 10^13/cm^2 (hole) to 2.00 × 10^13/cm^2 (electron) subject to the external electric fields of -1.0V/ Å and 1.0V/ Å for the G/SMoTe type. In addition, the optical absorption coefficient of the heterogeneous graphene/MoSSe is higher than 10^5/cm in the wavelength range from 550 nm to 800 nm. The results indicate that these graphene/MoXY heterostructures will have great applications in tunable nanoelectronic devices.